Algorithm Implementation Crochemore Perrin On The Dictionary Application Of Latin Terms Flora And Fauna Based On Android - Sandy, Bobby Aris; Hasugian, Paska Marto (Information Technology and Science (ITScience), 2020)
Searching is the process of selecting the information needed from a collection of data that already exists, data search is often also called a tablelook-up or store and retrieval information. Along with the development of technology that is now so very rapid, one of them is the Smartphone application. Smartphone applications that are currently in demand are increasing sharply, that is Android. Even though the presentation is limited to the screen, Smartphones are quite efficient for its users where the mobility is very high and affordable in all circles of society. used is the string search method. String search method is a string search process or often also called string matching. In the string matching process, there is the Crochemore perrin algorithm, which is an algorithm that factoring a pattern into two parts, namely Pattrenkiri and pattern right. This method is perfect for dictionary search applications of Latin terms flora and fauna.